El diccionario del mago : conoce todas las claves del universo de Harry Potter - Kronzek, Allan Zola (Escritura desatada., 2001)
Explores the true history, folklore, and mythology behind the magical practices, creatures, and personalities that appear in J.K. Rowling's Harry Potter books.